2011
DOI: 10.1177/000348941112000505
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Predictive Factors of Tracheobronchial Prosthesis Removal: Stent Brands are Crucial

Abstract: Even though endoscopic stent placement is a relatively safe and effective treatment for tracheobronchial stenoses, particularly in cases with malignancy, complications led to stent removal in about one third of cases. The type of stent chosen is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…24 Contrary to the study by Saad et al, 25 this finding was independent of the benign or malignant nature and precise cause of the stenosis, and independent of the type of prosthesis (for example, non-expandable, expandable covered, or uncovered). Buiret et al 24 reported the stability of each separate brand of prosthesis (the hazard ratio [HR] represents the probability of maintenance of the prosthesis): Ultraflex (HR: 1), covered Wallstent (HR: 2.496), Cook (HR: 8.701), Hanarostent (HR: 9.372), Aboulker (HR: 10.424), Tracheobronxane (HR: 10.626), Novatech Silmet (HR: 17.750), uncovered Wallstent (HR: 57.8), Novatech Y (HR: 88.268), and Rush Y (HR: 122.902). 24 Dasgupta et al 26 assessed 37 patients and reported that the longer a patient has an airway stent fitted, the greater the risk of complications.…”
Section: Predictors Of Stents Removalcontrasting
confidence: 56%
See 3 more Smart Citations
“…24 Contrary to the study by Saad et al, 25 this finding was independent of the benign or malignant nature and precise cause of the stenosis, and independent of the type of prosthesis (for example, non-expandable, expandable covered, or uncovered). Buiret et al 24 reported the stability of each separate brand of prosthesis (the hazard ratio [HR] represents the probability of maintenance of the prosthesis): Ultraflex (HR: 1), covered Wallstent (HR: 2.496), Cook (HR: 8.701), Hanarostent (HR: 9.372), Aboulker (HR: 10.424), Tracheobronxane (HR: 10.626), Novatech Silmet (HR: 17.750), uncovered Wallstent (HR: 57.8), Novatech Y (HR: 88.268), and Rush Y (HR: 122.902). 24 Dasgupta et al 26 assessed 37 patients and reported that the longer a patient has an airway stent fitted, the greater the risk of complications.…”
Section: Predictors Of Stents Removalcontrasting
confidence: 56%
“…19 In a separate series, it was reported that 21 of 48 prosthesis removals were justified by an apparent cure. 23 However, Buiret et al 24 only reported two removals that were justified by an apparent resolution of the stenosis.…”
Section: Haemoptysismentioning
confidence: 99%
See 2 more Smart Citations